PENGARUH TEMPERATURE, HOLDING TIME, DAN PENAMBAHAN Sn TERHADAP CACAT SHRINKAGE PADA PROSES SINTERING METAL INJECTION MOLDING AL-PP - Ahmad Rendi Maulana; Danang Yudistiro; Mochamad Asrofi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
Metal injection molding (MIM) is a relatively recent technological process used in the powder metallurgy industry, which is highly efficient and useful for the manufacture of large quantities of small and complex metal components. MIM consists of four basic steps consisting of mixing, injection molding, debinding, and sintering. Sintering to compact and increase the strength of metal powders and experience shrinkage (shrinkage). The purpose of this study was to determine the optimal combination of the MIM sintering process for the proportion of shrinkage defects by adding parameters Sn (%), temperature (℃), and holding time (hours). This study used an experimental design with the Taguchi method. The contribution factor obtained that the addition of the Sn parameter did not have a significant effect on the shrinkage of 14.48%, the temperature parameter had a significant effect on the shrinkage proportion of 68.92%, and the holding time parameter did not have a significant effect on the proportion of depreciation with a percentage of 6.27%. From the results, the optimal combination is the addition of Sn at level 3 (2%), the temperature at level 1 (450 ℃), and holding time at level 1 (1 hour).